The effect of online gaming intensity on students’ social behavior in physical education - Iqroni, David; Saputra, Endarman; Sulistiyo, Urip; Sofyan, Sofyan; Sofwan, Mohammad; Nugraha, Ugi; Ali, Muhammad (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to examine the effect of online gaming intensity on students' social behavior in Physical Education (PJOK) within a blended learning context. Quantitative correlational and regression design was employed, involving 74 tenth-grade students selected via simple random sampling. Data were collected using a validated Likert-scale questionnaire and analyzed using normality tests, Pearson correlation, and simple regression. The results indicate a very strong and significant relationship between online gaming intensity and social behavior (r = 0.848, p < 0.05), accounting for 71.9% of the variance. However, this study is limited to a single school context and does not account for other influencing factors such as family background and psychological conditions. The findings suggest that digital engagement is closely linked to students’ interaction patterns, particularly in blended learning contexts. educators must manage technology strategically to balance virtual and direct social interaction in blended learning environments.